Severe acute myocardial infarction and peripheral thrombosis in patient with bladder cancer - Gürbüz, Ahmet Seyfeddin; Kılıçgedik, Alev; Alsancak, Yakup; Efe, Süleyman Cagan; Öztürk, Semi; Düzenli, Mehmet Akif; Kırma, Cevat (Journal of Surgery and Medicine, 2017)
Cancer-associated thrombosis worsens the lives of patients substantially. Venous manifestations of cancer-associated thrombosis include deep vein thrombosis and pulmonary embolism. Arterial events include stroke and myocardial infarction. In this patient, myocardial infarction and cardiogenic shock are associated with diffuse coronary thrombosis together with peripheral thrombosis. He had surgery because of bladder carcinoma. Severe hypercoagulable condition probably facilitated by cancer itself and surgery caused multivessel coronary and peripheral intense thrombus burden. Intracoronary 10 mcg/kg tirofiban bolus and 15 mg tissue plasminogen activator (tPA) were administered respectively before revascularization and thrombectomy operation was performed. Complete revascularization was achieved.